2006
DOI: 10.1111/j.1742-4658.2006.05560.x
|View full text |Cite
|
Sign up to set email alerts
|

Ixocarpalactone A isolated from the Mexican tomatillo shows potent antiproliferative and apoptotic activity in colon cancer cells

Abstract: Physalis philadelphica Lam, commonly known as a tomatillo, is a staple of the Mesoamerican cuisine. In our laboratory, an ethyl acetate‐soluble extract and four withanolides [ixocarpalactone A (IxoA), ixocarpalactone B, philadelphicalactone B, and withaphysacarpin] were isolated. Studies conducted on Hepa‐1c1c7 hepatoma cells revealed that withanolides were potent inducers of quinone reductase, suggesting possible cancer chemoprotective activity. Here we evaluated the antiproliferative properties of the withan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
0
17
0
3
Order By: Relevance
“…It is a source of vitamins A and C, and it has been suggested that chemicals present in tomatillos, e.g. ixocarpalactone A, may have cancer chemopreventive properties (Choi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is a source of vitamins A and C, and it has been suggested that chemicals present in tomatillos, e.g. ixocarpalactone A, may have cancer chemopreventive properties (Choi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ixocarpolactones A (360) and B (361), isolated from P. philadelphica, exhibited significant inhibition of murine epidermal JB6 cell transformation (104) and ixocarpolactone A (360) present in the edible fruit of the plant showed potent antiproliferative and apoptotic activity in SW480 human colon cancer cells (247). Evaluation of 12 withaphysalins from P. minima and P. divaricata, including 331-334, showed only moderate cytotoxicity against the HCT-116 and H460 human cancer cell lines (154,186).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Accordingly, these bioactivity results should be considered with caution. Among the Physalis withanolides with an unmodified skeleton, potent cytotoxic activity has been reported for withangulatins A (511), B (94), and I (102), physangulin B (512), phyperunolide A (101), withaphysacarpin (195), philadelphicalactones A (197) and B (198), 18-hydroxywithanolide D (128), and withanone (513) (50,55,56,58,104,247).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…In addition, pectins with a high potential for use in the food industry (Morales-Contreras et al 2018) can be extracted from the fruit. Besides, the extract from leaves, stem, fruits and calyx has an important pharmacological potential, due to its high antibacterial (Khan et al 2016) and chemopreventive activity (Choi et al 2006).…”
Section: Palavras-chavementioning
confidence: 99%